PENGARUH PENDIDIKAN KESEHATAN METODE CERAMAH MEDIA FILM PENDEK TERHADAP PENGETAHUAN, SIKAP, DAN PRAKTIK IBU TENTANG DETEKSI DINI KASUS DIFTERI ANAK - Ronal S. Aditya; Nuzul Qur'aniati; Ilya Krisnana (Universitas Airlangga, 2014)
Introduction: Diphtheria is an infectious disease that is easily transmitted and dangerous because it can lead to death . Community participation in prevention is to improve their behavior that is able to recognize early symptoms , immediately take their child to a health facility if diphtheria is suspected , immediately equip their children immunized . Activities in the field of preventive health care in the form of counseling and education is a key priority to reduce the incidence of diphtheria . The purpose of this study is to explain the effect of health education media short film of the knowledge , attitudes , and practices of mothers about early detection of cases of diphtheria children in Sub Ivory SurabayaMethod: Design research is the study researchers used a pre - experiment . In this study, researchers used a simple random sampling technique performed on 54 mothers who have children who have received a complete DPT immunization in urban areas Ivory . Independenden variable is health education lecture method with the short film medium and the dependent variable is the knowledge , attitude , practice . Data collection using questionnaires and observation sheets . Data were analyzed with the Wilcoxon signed rank test statistic test ɑ < 0.05.Result: Based on the results of the study showed that health education lecture short film media affect knowledge significantly ( p = 0.000 ) , but it also contained a significant improvement on the attitude of the mother ( p = 0.000 ) , and practice of mothers about early detection of diphtheria also increased significantly ( p = 0.000).Discussion: Media short film may affect the knowledge , attitudes and practices so that the short film medium can be used as an alternative method of education . The need for the development of health education methods to increase the effectiveness of behavior change